PEMILIHAN SUPPLIER TERBAIK PENYEDIA BARANG CONSUMABLE MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (Studi kasus di Departemen Pengadaan Barang PT. PUSRI) - Irnanda Pratiwi; Hermanto MZ; Selvia Aprilyanti (Politeknik APP Jakarta, 2018)
Supplier selection is one of the most important activity of company’s procurement of goods and services function. One of the methods that can be used is Analytical Hierarchy Process (AHP). This research was conducted in Procurement Department of PT. PUSRI Palembang. This study focuses on suppliers of consumable goods because this goods most often purchased. The sample of the research were the employees in the department of goods procurement that handle the purchase of consumable goods. The final result of relative importance’s supplier selection criteria was found :First Priority is Price (0,42), Second Priority is Quality (0,33), Third Priority is Response (0,11) and Fourth Priority is Delivery (0,09) and last priority is customer care (0,08 ). The fisrt priority supplier is PT. Kokai Indo Abadi (0.47). The result of this study that PT. Kokai Indo Abadi is the most consistent company in the procurement of consumable goods so it can be included in the next auction.